DIFFERENTIAL PROPERTIES OF CURVES (International journal of artificial intelligence, 2026)
This article comprehensively discusses the differential properties of curves, particularly their parametric representation, arc length, curvature, normal and binormal vectors, Frenet formulas, and their geometric as well as practical interpretations. In addition, the main invariants describing the behavior of curves in space are analyzed.